Development and Validation of a Measure Assessing Sustainability of Tier 2 and 3 Behavior Support Systems. (April 2021) - Kittelman, Angus; Mercer, Sterett H.; McIntosh, Kent; Nese, Rhonda N.T.
Abstract: To identify the most effective strategies for implementing and sustaining Tier 2 and 3 behavior support systems, a measure of general and tier-specific factors hypothesized to predict sustained implementation is needed. To address this need, we conducted two studies examining the construct validity of the Advanced Level Tier Interventions Treatment Utilization and Durability Evaluation (ALTITUDE) measure: one assessing the content aspects of construct validity (Study 1) and one assessing the structural and external aspects of construct validity (Study 2). In Study 1, participants included an expert panel of 26 members who provided iterative feedback during measure development. The results showed strong content representativeness (content validity index = .93) for assessing elements indicating sustainability. In Study 2, participants were school personnel from 646 schools who completed the measure. The results showed model fit was good for both a three-factor correlated model (CFI = .98, RMSEA = .06, SRMR = .05) and Bifactor S-1 model with correlated Tier 2 and Tier 3 specific residual factors (CFI = .98, RMSEA = .06, SRMR = .05). In addition, ALTITUDE latent factors were found to have both convergent and discriminant evidence in relation to concurrent fidelity of school-wide positive behavioral interventions and supports (SWPBIS) implementation at Tiers 1, 2, and 3. This construct validity evidence will support the use of the ALTITUDE in identifying the strongest tier-general and tier-specific predictors of sustained implementation of Tier 2 and 3 behavior support systems.